Modulating physical properties of ASnF3 (A = K, Rb) perovskites under pressure: Insights for enhanced optoelectronic performance via first-principles - Md N.J. Rifat; Mohammad Nazmul Hasan; Jahid Kabir Rony; Md Murshidul Islam; Md Saiduzzaman; Minhajul Islam (Results in Materials)
Researchers have become interested in inorganic metal halide perovskites due to their widespread use in numerous engineering and scientific fields. Given their significance, the fundamental physical properties of metal halide fluoroperovskites ASnF3 (A = K, Rb) were investigated under applied pressure using density functional theory (DFT). The primary aim of this study is to enhance the distinct physical characteristics of these compounds by applying hydrostatic pressure, leading to a reduction in the electronic band gap. The Goldschmidt tolerance factor, formation energy, and Born stability criteria are used to verify the structural, thermodynamic, and mechanical stabilities, respectively. Furthermore, the lattice dynamical stability is confirmed by analyzing the phonon dispersion curves. The calculated lattice constant of RbSnF3 (4.77 Å) is in excellent agreement with the previously reported value of 4.765 Å. As pressure increases, leading to enhanced atomic contact, the lattice constant, volume, and bond length exhibit a steady decrease. Within the 0–9 GPa pressure range, KSnF3's band gap diminishes from 1.838 eV to 1.100 eV, while RbSnF3's band gap reduces from 1.835 eV to 1.010 eV. The band gap values exhibit a noticeable enhancement when calculated using the GGA-RPBE functional, yielding 2.080 eV for KSnF3 and 2.114 eV for RbSnF3 at 0 GPa pressure. The PDOS and TDOS was analyzed to see the contribution of electrons in each compound with applied pressure. A variation in optical properties is seen due to applied pressure which makes them efficient for optoelectronic devices. The conduction spectrum becomes higher with applied pressure due to the reduction in band gap. The mechanical properties of the compounds directly reflect their ductile and anisotropic characteristics, both of which are significantly influenced by external pressure. Analysis of the elastic functions indicates that these compounds become even more versatile for various potential applications when subjected to hydrostatic pressure. The hardness (HV) values follow the trend RbSnF3 > KSnF3, whereas the machinability index (B/C44) exhibits the opposite trend, with KSnF3 > RbSnF3 across the entire applied pressure range. We hope that this investigation makes a meaningful contribution to non-toxic halide perovskite materials research and serves as a foundation for future studies.